The shea butter tree's untapped riches - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The shea butter tree grows throughout savanna areas of West Africa and is prized for the oil extracted from its nuts, and for the sale of the nuts themselves. Unfortunately, processing and marketing difficulties mean that only 40% of the produce is...